2008
DOI: 10.2119/2007-00133.ramalho
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in Transgenic Mice Expressing the P301L Mutated Form of Human Tau

Abstract: The rTg4510 mouse is a tauopathy model, characterized by massive neurodegeneration in Alzheimer's disease (AD)-relevant cortical and limbic structures, deficits in spatial reference memory, and progression of neurofibrillary tangles (NFT). In this study, we examined the role of apoptosis in neuronal loss and associated tau pathology. The results showed that DNA fragmentation and caspase-3 activation are common in the hippocampus and frontal cortex of young rTg4510 mice. These changes were associated with cleav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 38 publications
0
14
1
Order By: Relevance
“…It has been suggested that activation of caspase-3 in the frontal cortex and hippocampus resulted in cleavage of tau in rTg4510 mice at 2.5 months (22), but the present study showed that amount of caspase-cleaved tau is very sparse in 2.5-month-old rTg4510 mouse neurons. Although Riesman et al demonstrated caspase-cleaved tau in early, tangle-like structures within neuronal somata and a myelinated axon in AD brain using IEM (5), TauC3 immunogold labeling was not observed in a 4-month-old rTg4510 mouse brain that had similar early tangle structures positive with MC1 and CP13 antibodies.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…It has been suggested that activation of caspase-3 in the frontal cortex and hippocampus resulted in cleavage of tau in rTg4510 mice at 2.5 months (22), but the present study showed that amount of caspase-cleaved tau is very sparse in 2.5-month-old rTg4510 mouse neurons. Although Riesman et al demonstrated caspase-cleaved tau in early, tangle-like structures within neuronal somata and a myelinated axon in AD brain using IEM (5), TauC3 immunogold labeling was not observed in a 4-month-old rTg4510 mouse brain that had similar early tangle structures positive with MC1 and CP13 antibodies.…”
Section: Discussioncontrasting
confidence: 88%
“…Because TauC3-positive neurons have been shown in both AD brains and those of rTg4510 mice (4, 6, 11, 21, 22), we also performed immunohistochemistry on rTg4510 mouse brains following formalin fixation and paraffin embedding. We first observed early changes of tau phosphorylation detected with the CP13 antibody at 2.5 months of age (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Studies on htau mice indicated that tau pathology may trigger an age-dependent learning impairment via disruption of synaptic function ( Figure 1) (Polydoro, Acker, Duff, Castillo, & Davies, 2009). Studies on rTg4510 tau transgenic mouse demonstrate caspase-3 activation, which substantiates the evidence linking caspase-3 and tau-mediated neurodegeneration (Calissano, Matrone, & Amadoro, 2009, Ramalho et al, 2008. A triple transgenic Alzheimer mouse model consisting PS1(M146V), APP(Swe), and tau(P301L) transgenes curbs caspase-9 activation, and attenuates the processing of APP and tau, thus decreasing the number of NFTs and extracellular deposits of Aβ entailed with the progression of this disease (Calissano et al, 2009, Rohn et al, 2008.…”
Section: Neuropathology In Animal Modelsmentioning
confidence: 54%
“…For example, overexpressing human mutant tau P301L in mice results in apoptosis, caspase-3 activation, and appearance of caspase truncated tau (de Calignon et al , 2010; Ramalho et al , 2008). Similarly, overexpression of human 4R tau results in caspase activation, although total numbers of caspase bearing neurons are low (de Calignon et al , 2010).…”
Section: The Role Of Tau In Cellular Dysfunctionmentioning
confidence: 99%
“…However, similar to human studies, transgenic animal models of tauopathy suggest that formation of caspase truncated tau occurs prior to tau aggregation and correlates with cognitive decline. In fact, in P301L mice, caspase cleavage of tau proceeds neurofibrillary tangle formation (de Calignon et al , 2010; Ramalho et al , 2008), and is coincident with the beginnings of cognitive impairment (Ramalho et al , 2008). Furthermore, animal models confirm in-vitro findings that caspase truncated tau can seed filament formation of full length tau (Gamblin et al , 2003; Rissman et al , 2004).…”
Section: The Role Of Tau In Cellular Dysfunctionmentioning
confidence: 99%